Quantum of solace [videorecording (DVD)] - Forster, Marc, 1969-; Craig, Daniel, 1968-; Kurylenko, Olga, 1979-; Dench, Judi, 1934-; Fleming, Ian, 1908-1964 (Distributed by 20th Century Fox Home Entertainment, 2009)
Bond is driving from Lake Garda to Siena, Italy with the captured Mr. White in his car's luggage compartment. Bond is attacked by chasing henchmen, but evades them. Bond and M interrogate White regarding his organisation, Quantum. Bond learns that a was sent to kill Camille Montes, but does not succeed. When a bodyguard to the British Prime Minister is accidentally killed, M has Bond's passports and credit cards revoked. Bond and Camille discover Quantum is blockading Bolivia's supply of fresh water. Believing that Bond has become a threat to both friend and foe, M orders him to disarm and end his activities in Bolivia. He defies her and escapes. Bond meets CIA agent Felix Leiter at a local bar. M reveals that Leiter has been promoted at the CIA. M then tells Bond that MI6 needs him and fully reinstates him as an agent. Bond walks off into the night telling M that he never left.